Penerapan Customer Relationship Management Untuk Menjaga Loyalitas Pelanggan Waroeng Steak and Shake (WSS) di Kota Malang. - nisa, Choirun; Zain, Djumilah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to find the influence of customer orientation, customer relationship management (crm) organization, knowledge management, to customer royalty Waroeng Steak and Shake (WSS) in Malang. Sampling technique that use in this study was purposive sampling and obtained a sample of 100 respondents who are customers of Waroeng Steak and Shake (WSS). Data analysis was perfomed by using the classical assumption and hypothesis testing using multiple linear regression analysis. The results of this study indicate that customer relationship variable and knowledge management are not significantly influence to customer loyalty. While the customer relationship management organization is the only variable that significantly the customer loyalty.